PEMBELAJARAN MATEMATIKA SMP DENGAN PENDEKATAN APTITUDE TREATMENT INTERACTION BERBASIS PORTOFOLIO - Sutama, Sutama (MAJALAH ILMIAH PEMBELAJARAN, 2009)
This research and development aimed to compile model study of mathematics in SMP with interaction treatment aptitude (ATI) approach based on portfolio. Data is e collected by observation, interview, and FGD. The research participation is teachers, students, educationist, and policy makers. This research is located in four public SMP and four SMP private sector of Surakarta. The data is analyzed using interactive cycle of data collecting, reduction data, data presentation, and withdrawal of verification or node. The research findings can be summarized that the development of mathematics model study with ATI approach based on portfolio and its activities is started from antecedent phase, central activity phase, and last activity phase, with the documentation of all students. Third step is conducted in immeasurable class setting, according to the model of classical, group, and individual context. A small team learning group which has five member of students with the difference ability (1 is high, 2 is middle, and 1 lowering) with peer tutor in rotation. The antecedent activities include a) review, b) early motivation, and c) apperception. The activity focused on the development of applying concept. The last activity includes reviewing resume items and conducting the follow-up.